A novel biosensor for the ultrasensitive detection of the lncRNA biomarker MALAT1 in non-small cell lung cancer - Mei Chen (Nature Portfolio, 2021)
Abstract Long non-coding RNAs (lncRNAs) have been proposed as diagnostic biomarkers for the screening of non-small cell lung cancer and monitoring disease progression. Accordingly, new, rapid, and cost-effective lncRNA biosensors that can be used clinically are urgently needed. Herein, a novel effective and ultrasensitive electrochemical biosensor was developed based on a gold nanocage coupled with an amidated multi-walled carbon nanotube (Au NCs/MWCNT-NH2)-decorated screen-printed carbon electrode (SPCE). Because of its large surface area, superior conductivity, and excellent biocompatibility, this SPCE Au NCs/MWCNT-NH2 lncRNA biosensor showed a wide linear range (10–7–10–14 M) and low limit of detection limit (42.8 fM) coupled with satisfactory selectivity and stability. Compared to traditional RT-PCR, the proposed method exhibits acceptable stability, good selectivity, is simpler to operate, has faster detection, and uses less costly raw materials. In summary, this biosensor may be a powerful tool for detecting lncRNAs for efficient clinical prognosis and cancer diagnosis.